Relationship between Gender and Education Level with Quality of Life of Elderly at Nursing Home in Indonesia - Iswatun, Iswatun; Kusnanto, Kusnanto; Mirauna, Risma; Nasir, Abd; Sairozi, Ali; Umam, Khotibul (International Journal of Psychosocial Rehabilitation, 2020)
Aging is a transition period where people experience changes, not only in physical health, but also in social roles and wellbeing. This study aims to identify gender relations and education with the quality of life of the elderly who live at UPT Tresna Werdha Social Services in Pasuruan in Lamongan. This study used a cross- sectional design and a healthy and cognitive elderly population registered as members of the Tresna Werdha Pasuruan Social Services Unit in Lamongan as many as 50 people, taken using total sampling techniques. Data were analyzed by multiple linear regression statistical tests with a significance level of α <0.05. Statistical correlation test results were obtained by multiple linear regression had values ρ = 0.447 so that ρ> 0.005, meaning there is no relationship between gender with the quality of life of the elderly. Likewise, there is no relationship between the level of education with the quality of life of the elderly, the value of ρ = 0.059 so that ρ> 0.005. Gender and education level factors are not related to the quality of life of the elderly so more research is needed, which requires more respondents to obtain significant results.